Periodic components of EEG power spectrum reveal the effect of long-term modulated acoustics on chronic tinnitus - Chanlin Yi; Rui Zhang; Haoyang Yu; Chen Liu; Jiamin Zhang; Min Ao; Yong Zhao; Dezhong Yao; Peng Xu; Fali Li (Brain-Apparatus Communication)
Background: Acoustic therapy modulates neural oscillatory rhythms in various brain regions, thereby alleviating symptoms associated with tinnitus. Neural oscillation serves as an efficient mechanism in the brain, synchronizing information and coordinating temporal processes to facilitate effective integration and processing of information through a combination of harmonic and relaxation oscillations. The presence of 1/f noise, however, can obscure the detection of oscillations and diminish their biological interpretability, thereby impeding the investigation of neuroplasticity in tinnitus patients during acoustic therapy. Methods: This study proposes extracting the periodic components based on neural power spectra decomposition to accurately capture narrow-band activities. Subsequently, we investigated the neuroplasticity changes manifested by periodic oscillations during a 75-day long-term acoustic intervention. Results: The results indicate that the periodic component was more sensitive in capturing treatment-induced neural remodelling. The periodic components in alpha/beta progressively diminished, with their observed prominence becoming negligible by the end of the treatment, a trend consistent with the improvement of clinical symptoms. Changes in periodic components exhibited a stronger linear correlation with THI decline, and the interindividual agreement was greater than that of PSD. Conclusion: This study provides novel insights into the impact of long-term acoustic intervention on neural oscillations in tinnitus patients.